Altered Cortico–Striatal Functional Connectivity During Resting State in Obsessive–Compulsive Disorder - Calzà, Jessica; Gürsel, Deniz A.; Schmitz-Koep, Benita; Bremer, Benno; Reinholz, Lena; Berberich, Götz; Koch, Kathrin (Frontiers in Psychiatry, 2019)
Background: Neuroimaging studies show that obsessive-compulsive disorder (OCD) is characterized by an alteration of the cortico-striato-thalamo-cortical (CSTC) system in terms of an imbalance of activity between the direct and the indirect loop of the CSTC. As resting-state functional connectivity studies investigated only specific parts of the CSTC in patients with OCD up to now, the present study aimed at exploring functional connectivity in the CSTC as a whole. Methods: We investigated potential alterations in resting-state functional connectivity (FC) within the CSTC system in 44 OCD patients and 40 healthy controls by taking into consideration all relevant nodes of the direct and indirect CSTC loop. Results: Compared to healthy controls, OCD patients showed an increased FC between the left subthalamic nucleus (STN) and the left external globus pallidus (GPe), as well as an increased FC between the left external globus pallidus and the left internal globus pallidus (GPi). Conclusion: These findings may contribute to a better understanding of the OCD pathophysiology by providing further information on the connectivity alterations within specific regions of the CSTC system. In particular, increased FC between the STN and the left GPe may play a major role in OCD pathology. This assumption is consistent with the fact that these regions are also the main target sites of therapeutic deep brain stimulation in OCD.